2017
DOI: 10.1126/sciadv.1602762
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity recovery following delta-wide measures for flood risk reduction

Abstract: We show that biodiversity recovery was successfully combined with flood risk reduction interventions at the river delta scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Finally, our study was limited to the effect of interventions with respect to water level lowering. We did not consider other indicators, such as economic, ecological or societal costs and benefits, as was done by Straatsma et al (2019) (albeit without addressing uncertainty). Multidisciplinary and multi-sectoral assessment of interventions including uncertainty is recommended to determine tradeoffs in river management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study was limited to the effect of interventions with respect to water level lowering. We did not consider other indicators, such as economic, ecological or societal costs and benefits, as was done by Straatsma et al (2019) (albeit without addressing uncertainty). Multidisciplinary and multi-sectoral assessment of interventions including uncertainty is recommended to determine tradeoffs in river management.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage computational models can bring to decision-making for river engineering is an assessment of the impact of the planned intervention on hydraulics, such as water levels, flow velocities and the morphodynamic response of the river bed. While hydraulic effects are not the only impact of interventions (see, for example, Straatsma et al, 2017, for effects on biodiversity), they are considered important: for the 39 interventions of the EUR 2.3 billion "Room for the River" programme in the Netherlands, the hydraulic effect as predicted by models was a precondition for any design "to be taken seriously at all" (Klijn et al, 2013). Mosselman (2018) reported that quantified, large uncertainty in flood water levels is sometimes played down when assessing effects, under the assumption that systematic errors cancel out when subtracting the intervention case from the reference case.…”
Section: Introductionmentioning
confidence: 99%
“…; Straatsma et al. ) and that of recent debate on the relation between the evolution of initially rootless land plants in the Palaeozoic and associated appearance of meandering and anastomosing rivers (Santos et al. ; Davies et al.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, stakeholder sessions have not been repeated to assess their variation in outcomes because they are time-consuming. Alternatively, the variation in stakeholder processes could be modeled using game theory, or agent-based models, but this is still in its infancy: Samsura et al (2010) used game theory to extract the strategic decisions used by stakeholders, Strager and Rosenberger (2006) integrated GIS with stakeholders preferences in a spatial multicriteria analysis to identify high priority areas for land conservation, and Becu et al (2003) created an agent-based system of a catchment in northern Thailand, including farmers' individual decisions. They attributed the agents with the availability of water, land, cash, and labor force and focussed on decisions made by farmers, instead of including the preferences made by other stakeholders.…”
Section: Discussionmentioning
confidence: 99%